Urinary capillariosis in a free-ranging Marsican brown bear (Ursus arctos marsicanus) - Mariacher, Alessia; Eleni, Claudia; Fico, Rosario; Perrucci, Stefania (Zenodo, 2018)
Mariacher, Alessia, Eleni, Claudia, Fico, Rosario, Perrucci, Stefania (2018): Urinary capillariosis in a free-ranging Marsican brown bear (Ursus arctos marsicanus). International Journal for Parasitology: Parasites and Wildlife 7 (3): 429-431, DOI:10.1016/j.ijppaw.2018.11.002, URL: http://dx.doi.org/10.1016/j.ijppaw.2018.11.002